Airfoil, Blade Perancangan Bilah Taperless Menggunakan Airfoil NACA 2412 Pada Horizontal Axis Wind Turbine (HAWT) The Sky Dancer 500 Watt - Teguh Adipranata; Oleh Oleh (Peneliti.net, 2022)
Abstract The wind speed in Indonesia is only around 3 meters/s to 12 meters/s, it is quite difficult to generate electricity on a large scale, it also makes the utilization of wind energy still very low. However, the wind potential in Indonesia is available almost all year round, so there is a possibility of developing technology to utilize this energy with some of the limitations mentioned above. Modifications of windmills need to be carried out which are adapted to low wind speed conditions to be able to produce optimal electrical energy. Therefore, a HAWT (Horizontal Axis Wind Turbine) design was made using a NACA airfoil that has a high Cl/Cd value to produce 500 W of power at wind speeds of 1 meter/s – 12 meters/s. The research was conducted in 3 stages. The first step is the calculation to determine the radius, chord, and twist of the blade. The two initial design stages of the blade are carried out in a simulation using QBlade software to determine the NACA airfoil used and determine the performance coefficient and the resulting power. The three stages of blade design use Solidworks software which produces a 3D blade design. The design results produce a HAWT blade with a taperless NACA 2412 airfoil with a blade radius of 0.75 m, 0.12 m chord width, and a twist angle of 5.42°-15.46°. At a wind speed of 10 m/s, the blades have a maximum Cp of 49%, maximum power of 923 W at an angular speed of 1000 rpm, and a minimum power of 90 W at an angular speed of 200 rpm. The average power generated is 567W.